Gaya Kepemimpinan Demokratis Kepala Sekolah dalam Meningkatkan Mutu Lulusan SMK: Studi Literatur - Fitri Jalal; Ernawati Ernawati; Jonni Mardizal (Journal on Education, 2024)
The principal's leadership style plays an important role in determining the quality of graduates of Vocational High Schools (SMK). This study aims to analyze the influence of the principal's democratic leadership style in improving the quality of graduates through a literature approach. The method used is a literature study, by reviewing relevant research published in the last five years. The results of the study indicate that a democratic leadership style that emphasizes collaboration, active participation, and open communication is able to create a conducive school environment for the development of student competencies. Principals who apply this leadership style tend to be more successful in building harmonious relationships with teachers, students, and the community, thus supporting the achievement of better quality education. In addition, democratic leadership encourages increased innovation in learning and character development of students that are in accordance with the needs of the world of work. This study makes an important contribution in identifying leadership values ​​that are relevant to the development of educational policies and practices in SMK.